The Effect of Different Fluoride Concentrations and pH of Dentifrices on Plaque and Nail Fluoride Levels in Young Children - Buzalaf, M. A. R.; Vilhena, F. V.; Iano, F. G.; Grizzo, L.; Pessan, Juliano Pelim [UNESP]; Sampaio, F. C.; Oliveira, R. C. (Karger, 2009)
To evaluate the influence of dentifrice pH and fluoride (F) concentration on F uptake by plaque and nails, two sets of 5-to 6-year-old children were randomly allocated into four groups, according to the type of dentifrice they had been using for 1 year: (1) experimental liquid dentifrice (ELD), 1,100 ppm F, pH 7.0; (2) ELD, 1,100 ppm F, pH 4.5; (3) ELD, 550 ppm F, pH 4.5, and (4) commercial toothpaste, 1,100 ppm F, pH 7.0. In one set of children, nails were clipped. In the second, plaque samples were collected 1 h after the last use of dentifrice. F concentration in plaque and nails was analyzed. Plaque F concentration was significantly lower in group 4 than in groups 1-3. Nail F concentration was significantly higher in group 4, and significantly lower in group 3, than in group 1 or 2. Plaque F uptake was influenced significantly by dentifrice consistency and nonsignificantly by pH and F concentration. Reduction of dentifrice pH did not affect nail F concentration. Copyright (C) 2009 S. Karger AG, Basel
Keywords: Dentifrices; Fluoride; Nails; Plaque